2019
DOI: 10.1002/jgt.22491
|View full text |Cite
|
Sign up to set email alerts
|

A Ramsey property of random regular and k‐out graphs

Abstract: In this study we consider a Ramsey property of random d‐regular graphs, G(n,d). Let rgoodbreakinfix≥2 be fixed. Then w.h.p. the edges of G(n,2r) can be colored such that every monochromatic component has order o(n). On the other hand, there exists a constant γgoodbreakinfix>0 such that w.h.p., every r‐coloring of the edges of G(n,2r+1) must contain a monochromatic cycle of length at least γn. We prove an analogous result for random k‐out graphs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Another possible direction for further study involves replacing large monochromatic components with long monochromatic paths. Letzer showed that in every 2-coloring of G(n, p) with p = ω (1) n , there is w.h.p., a monochromatic cycle (path) of order at least (2/3 − o(1))n. Bennett, DeBiasio, Dudek, and English [5] generalized this result showing that if p = ω (1) n k−1 , then a.a.s. there is a monochromatic loose-cycle (loose-path) of order at least ( 2k−2 2k−1 − o(1))n in every 2-coloring of H k (n, p).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible direction for further study involves replacing large monochromatic components with long monochromatic paths. Letzer showed that in every 2-coloring of G(n, p) with p = ω (1) n , there is w.h.p., a monochromatic cycle (path) of order at least (2/3 − o(1))n. Bennett, DeBiasio, Dudek, and English [5] generalized this result showing that if p = ω (1) n k−1 , then a.a.s. there is a monochromatic loose-cycle (loose-path) of order at least ( 2k−2 2k−1 − o(1))n in every 2-coloring of H k (n, p).…”
Section: Discussionmentioning
confidence: 99%
“…For hypergraphs, Bennett, DeBiasio, Dudek, and English [5] proved that if G is an (r − 1)-uniform hypergraph on n vertices with e(G) ≥ (1 − o(1)) n r−1 , then mc r−1 (G) ≥ (1 − o(1))n and mc r (G) ≥ ( r−1 r − o(1))n. As for random graphs, it was independently determined in [2], [8] that with high probability 2 , mc r (G(n, p)) ≥ (1−o(1)) n r−1 provided p = ω (1) n , and it was determined (using the result mentioned in the previous paragraph) in [5] that mc r (H r (n, p)) ≥ (1 − o(1))n provided p = ω (1) n r−1 , and mc r (H r−1 (n, p)) ≥ (1 − o(1)) (r−1)n r provided p = ω(1) n r−2 . All of these results for random graphs use the sparse regularity lemma and thus only provide weak bounds on the error terms.…”
Section: Introductionmentioning
confidence: 99%
“…which by the assumption implies that G has a monochromatic component of order at least t. Without loss of generality suppose this monochromatic component corresponds to C 1 1 and thus by the comments above, we have that C 1 1 has degree at least t.…”
Section: Observation 21 (Duality)mentioning
confidence: 91%
“…Note that for 1 ≤ r ≤ k, mc r (G) = n = mc r (K k n ) if and only if the r-shadow of G is complete. 1 On the other hand, as first noted by Gyárfás and Sárközy [11], when r > k = 2 it is surprisingly possible for mc r (G) = mc r (K n ) provided G has large enough minimum degree. See [11], [17], and [10] for the best known results on this minimum degree threshold in the case k = 2, and [3] for a precise result on the minimum codegree threshold in the case r = k + 1 ≥ 4.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation